2018
DOI: 10.5812/jhealthscope.58267
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Welders Exposure to the Released Contaminated Gases in Different Types of Welding Processes in a Steel Industry

Abstract: Background: Exposure to the evaporated gases during the welding process has short-or long-term effects on welders' health. Assessment of the risk by identifying and determining the chemical risk rating might be a useful tool for the experts in industrial hygiene. Objectives: The present study aimed at evaluating the exposure of welders to welding gases in seven welding types in the Steel Industry. Methods: The present study was conducted in one of the factories of the steel industry in 2017. Seven types of wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Mehrifar, et al , also showed that welders working in another steel industry are also exposed to concentrations of O 3 , CO and NO 2 higher than the TLV-TWA. 36…”
Section: Discussionmentioning
confidence: 99%
“…Mehrifar, et al , also showed that welders working in another steel industry are also exposed to concentrations of O 3 , CO and NO 2 higher than the TLV-TWA. 36…”
Section: Discussionmentioning
confidence: 99%
“…Welding is a process in which two or more metals are bonded through pressure, heat, or both [12]. Shielded metal arc welding (SMAW) is a metal bonding process in which the arc between the electrode and the work piece is generated.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with equations ( 3) to (8), as well as for equations ( 1) and ( 2), the results obtained in the studies were processed. After processing the results of the experiment, the level of significance of each coefficient at α = 0.05 was de termined.…”
Section: Results Of Studying Carbon Monoxide Formation During Gas Welding Processesmentioning
confidence: 99%
“…Analyzing the derived mathematical dependences (3) to (8), it is necessary to pay attention to the fact that electric arc welding is characterized by a much higher rate of CO formation from the beginning of the process (8.5 mg/s), then this speed is reduced in 20 s by 2 times (to 4.5 mg/s). After 90 s, the speed becomes almost constant, to 2 mg/s.…”
Section: Results Of Studying Carbon Monoxide Formation During Gas Welding Processesmentioning
confidence: 99%
See 1 more Smart Citation